2022
DOI: 10.3389/fmicb.2022.993451
|View full text |Cite
|
Sign up to set email alerts
|

Potential application of the probiotic Bacillus licheniformis as an adjuvant in the treatment of diseases in humans and animals: A systematic review

Abstract: The use of Bacillus licheniformis as a probiotic has increased significantly in recent years. Published reports demonstrate that it provides multiple benefits for health. Although there are already studies in humans and is marketed, it is mostly used in the veterinary industry still. However, its benefits could be extrapolated to humans in future. This review addresses the application of B. licheniformis, its sporulation, mechanisms of action, and its role in the resolution, treatment, and prevention of differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…The possession of PKS genes is very common in Bacillus species, including in B. subtilis and B. licheniformis . In this study, and others, it has been shown that B. licheniformis is able to synthesize different antimicrobial compounds that can inhibit the growth of specific bacteria, which could be useful to tackle certain diseases associated with animals and plants in downstream applications with the strain [ 55 ]. The B. licheniformis CG1 isolate was predicted to have secondary metabolite clusters associated with the synthesis of lichenysin and lichenicidin, which is consistent with the literature [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…The possession of PKS genes is very common in Bacillus species, including in B. subtilis and B. licheniformis . In this study, and others, it has been shown that B. licheniformis is able to synthesize different antimicrobial compounds that can inhibit the growth of specific bacteria, which could be useful to tackle certain diseases associated with animals and plants in downstream applications with the strain [ 55 ]. The B. licheniformis CG1 isolate was predicted to have secondary metabolite clusters associated with the synthesis of lichenysin and lichenicidin, which is consistent with the literature [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…B. paralicheniformis exhibits the closest phylogenetic relationship to B. licheniformis , 19 a probiotic extensively employed in human health, veterinary practices, and aquaculture. 20 There is a paucity of research conducted on B. paralicheniformis ; however, the existing evidence indicates that it exhibits the ability to synthesize cholesterol oxidase and lipase, enabling efficient degradation of cholesterol. 21 Additionally, it demonstrates a protective effect on porcine jejunum epithelial cells against oxidative damage induced by H 2 O 2 through the activation of the MAPK pathway.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally found in soil, water and various natural environments ( Parkinson 2019 ). B. licheniformis has gained substantial attention due to its versatile metabolic capabilities and potential applications in industry and biotechnology ( Muras et al, 2021 , Ramirez-Olea et al, 2022 ). It is recognized to produce an array of secondary metabolites including certain antibiotics with antimicrobial activity ( Mondol et al, 2013 , Muras et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%